2001
DOI: 10.4049/jimmunol.167.4.2257
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tolerance to Lipopolysaccharide and Mycobacterial Components in Chinese Hamster Ovary/CD14 Cells Is Not Affected by Overexpression of Toll-Like Receptors 2 or 4

Abstract: Down-regulation of cell surface expression of Toll-like receptor (TLR) 4 following LPS stimulation has been suggested to underlie endotoxin tolerance. In this study, we examined whether overexpression of TLR2 or TLR4 would affect the ability of cells to become tolerant to LPS or the mycobacterial components, arabinose-capped lipoarabinomannan (LAM) and soluble tuberculosis factor (STF). To this end, Chinese hamster ovary/CD14 cells stably transfected with a NF-κB-dependent reporter construct, endothelial leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
146
1
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 71 publications
(91 reference statements)
13
146
1
2
Order By: Relevance
“…Forced overexpression of TLR4 in macrophages results in increased proinflammatory cytokine secretion in response to LPS (23). Increased expression of TLR4 has also been reported in several experimental models of inflammation including intestinal inflammation (39) and respiratory syncytial virus-induced inflammation (40).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Forced overexpression of TLR4 in macrophages results in increased proinflammatory cytokine secretion in response to LPS (23). Increased expression of TLR4 has also been reported in several experimental models of inflammation including intestinal inflammation (39) and respiratory syncytial virus-induced inflammation (40).…”
Section: Discussionmentioning
confidence: 83%
“…LPS transduces signals via TLR4 while forced overexpression of TLR4 results in increased cytokine secretion in response to LPS (23). Therefore, the aim of the present study was to examine the role of CRF and its related peptides UCN1 and UCN2 on the regulation of TLR4 expression by macrophages.…”
mentioning
confidence: 98%
“…8,[10][11][12] In light of the finding that 10 cellular responses to different microbial stimuli are mediated by different 11 TLRs, studies were initiated to determine whether, in analogy to LPS tolerance, pretreatment with microbial non-LPS stimuli also induces hyporesponsiveness to subsequent restimulation. Indeed, it has been reported that stimulation with prototypical ligands for TLR-2 (+TLR-1 or -6), [13][14][15][16][17][18] TLR-4, TLR-5 19 and TLR-9 20,21 also induces this state of hyporesponsiveness towards subsequent stimulation with the same ligand. Moreover, stimuli signalling via TLR-2 and TLR-4, 14,15 as well as TLR-4 and TLR-9, 20 can substitute for each other, mediating cross-tolerance in vitro as well as in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional adaptor proteins have been identified which mediate TLR-specific signal transduction. [24][25][26][27][28][29] Thus, in TLR-4 signalling, toll-interleukin 1 receptor domain containing adaptor protein (TIRAP)/ MyD88 adaptor like protein (Mal) 13 can partly substitute for MyD88. Furthermore, TLR-3 and TLR-4 make use of 14 toll-interleukin 1 receptor domain containing adaptor inducing interferon beta (TRIF)/toll-interleukin 1 receptor domain (TIR) containing adaptor molecule (TICAM)-1 and TRIF related adaptor molecule (TRAM) 15 /TICAM-2, thereby inducing interferon (IFN)-b, which in turn activates a set of IFN-inducible genes in a paracrine mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation